Delegacia de polícia - defesa da mulher? um enfoque dialógico - Melo, Rosineide de (2001)
The objective of this piece of work concentrates in three leading questions: verifying how the reformulation process from the oral to the written contributes to the constitution of heterogeneous meanings in discourse; identifying the stable elements of the utterances which not only compose theme, compositional form and style, but also characterize the discursive activity of the police department for the defense of women and pinpointing linguistic and extralinguistic tracks which reveal the voices in the discourse of the institution researched. The data examined are oral reports of the women, victims of violence, Who go to the Police Station for the Defense of Women in order to make a statement, written in the Boletim de Ocorrência and in the Termo Circunstanciado (Forms in which the statement is offically registered) made by the official police notary officer. To observe the institution, it is necessary to know its genesis. For this reason, I brought about the origins of the feminist movements, the political and social conquests obtained by women, including the creation of those special police stations to attend women in need. As theoretical foundation, I adopt the notions of Bakhtin and his circle about genre and dialogism and I discuss how these elements integrate themselves and are noticed in the discourse of the Police Station for the Defense of the Women. The reported speech in the process of reformulations appears as the main category of analysis. Quoting the three objects, we notice that the reformulation process from the oral to the written, from the day-to-day language of the women to the legal/juridical language (in the documents) modifies, erasing or adding information, i.e.:, gives more meanings to the utterance. The study permitted us to reflect upon the social roles that victims and notary officers assume in the interaction and the context of society; offering us the opportunity of verifying how the various voices organize themselves, characterizing the activity in the Police Station for the Defense of Women and, last but not least, it was possible to observe that, otherwise, the Police Station does not yet defend the women, but, supports, in its discursive practices, the discriminating values against them